Traditional Wedding of Kubachi Village of Republic of Dagestan - F. A. Gadzhalova (Научный диалог)
Traditional wedding of an ethnic group of Dargins - kubachins, residents of Kubachi, the known village of the Republic of Dagestan is considered. The main stages of traditional wedding, which lasted from 3 to 7 days, are characterized. Attention is paid to the ethno-local features of the wedding ceremony, spectacular components. It is noted that the main actions of wedding take place in the house of a bride and groom. The description of the traditional dress of Kubachi bride is given, which consists of a brocade dress, head cover, embroidered with gold threads, silver jewelry and other elements of the festive clothing complex. The bride’s dowry consists of the original traditional copper utensils: large ( мучIал ) and small ( къуткъа ) aquifer jugs, ritual vessels ( нукьнус ). The novelty of the study is seen in the fact that in the scientific literature there is no description of the traditional wedding of Kubachi village. It is emphasized that scientists have repeatedly noted the locality of traditions in the economic life of the kubachins, in metalworking, women’s clothing, ritual culture, oral folk art, arts and crafts, but wedding traditions were concerned only partially. The relevance of the study is due to the importance of fixation and preservation of information about the unique customs and rituals of the peoples of Dagestan.